أثر توجيه القراءات القرآنية المتواترة في بناء الخطاب العقدي في سورة الشورى: The Impact of the Interpretation of Mutawātir Qur'anic Qirāʾāt on the Ideological Construction of Doctrinal Discourse in Sūrah al-Shūrā - فاطمة سعد النعيمي (الدراسات الإسلامية, 2024)
This study examines the impact of the interpretive guidance of mutawātir Qur’anic readings in shaping the doctrinal discourse within Sūrah al-Shūrā, with a particular focus on the nuanced shift in religious discourse between Makki and Madani sūrahs. In the Makki sūrahs, including Sūrah al-Shūrā, the Qur’an addresses polytheists who reject the doctrine of monotheism and deny the Prophethood of Muhammad (peace be upon him), necessitating a tone marked by firmness and confrontation. In contrast, the Madani sūrahs primarily address a believing community and thus adopt a more instructive, composed style. The research aims to elucidate the role of interpretive guidance (tawjīh) of Qur’anic readings in constructing the doctrinal framework of Sūrah al-Shūrā, while also exploring the broader influence of such readings across Makki and Madani contexts. Employing the inductive method to gather variant readings, the descriptive method for classification and presentation, and the analytical method for evaluating their theological implications, the study demonstrates that Mutawātir readings significantly contribute to the clarification of subtle meanings in the Qur’anic text. This, in turn, enhances a comprehensive and profound understanding of the doctrinal content, particularly concerning the divine names and attributes. Moreover, the multiplicity of readings reflects the linguistic and semantic inimitability (iʿjāz) of the Qur’an, offering diverse yet non-contradictory interpretative dimensions that underscore the uniqueness of the Qur’anic discourse.